The Impact of New Graduate Nurse Transition Programs on Competency Development and Patient Safety: An Integrative Review. (October 2018) - Tyndall, Deborah E.; Firnhaber, Gina C.; Scott, Elaine S.
Abstract : Stronger evidence on the value of new graduate nurse transition programs is needed to justify the cost and warrant expansion of these programs to more health systems. The aim of this integrative review was to critically analyze published research on the relationship between new graduate nurse transition programs and patient safety outcomes. Limited evidence was found on actual safety improvement; rather, transition programs have predominately measured the development of competency as a process outcome variable for improving patient safety. A systems model is proposed to guide future research examining structure, process, and outcome variables, linking transition programs with patient outcomes.